TRICHODERMA ASPERELLUM: A TREASURE HOUSE OF BIOACTIVE COMPOUNDS WITH ANTAGONISTIC ACTIVITY AGAINST Rhizoctonia bataticola, A CAUSAL AGENT OF DRY ROOT ROT IN CHICKPEA - Meghana S Patil; Gururaj Sunkad; Yenjerappa S. T.; Sunil A. Kulkarni; Satyanarayana Rao (Journal of Animal and Plant Sciences, 2023)
Dry root rot is a major threat to chickpea production globally. The disease is caused by Rhizoctonia bataticola. The recent rise in global temperature and worsening of drought spells has aggravated dry root rot outbreaks in chickpeas. To combat this necrotrophic pathogen, the present study was conducted to inhibit the pathogen by using potential plant growth-promoting microorganisms (PGPMs). Forty isolates of endophytic fungal PGPMs were isolated from healthy plant parts of chickpeas in a potato dextrose agar medium. Isolates were screened for antagonistic potential and bioactive compound production against R. bataticola. Using ITS genes BLAST analysis, the putative endophytic fungal PGPM was identified at the molecular level. Finally, the extraction of bio-active compounds and metabolic profiling was carried out by solvent extraction method and GC-MS/MS technique, respectively. Among forty isolates, FEPGPM-34 produced the maximum concentration of bio-active compounds with the highest percent mycelial inhibition of 74.61. Through molecular characterization and BLAST analysis, the isolateFEPGPM-34 was identified as Trichoderma asperellum. GC-MS/MS analysis of T. asperellum extract showed the presence of 65 compounds at different retention times and mass to charge (m/z) ratios with 13 compounds exhibiting antimicrobial properties. Hence, PGPMs can be exploited for managing dry root rot disease.
Keywords: Dry root rot; GC-MS; Metabolic profiling; Rhizoctonia bataticola; Trichoderma asperellum